Elucidating Tricin-Lignin Structures: Assigning Correlations in HSQC Spectra of Monocot Lignins - Lan, Wu (Polymers (Basel), 2018)
Tricin [5,7-dihydroxy-2-(4-hydroxy-3,5-dimethoxyphenyl)-4H-chromen-4-one] is a flavone that has been found to be incorporated in grass lignin polymers via 4′–O–β coupling. Herein, we investigated the tricin-lignin structure using nuclear magnetic resonance (NMR) methods by comparing the 1H–13C heteronuclear correlation (HSQC) NMR spectra of the isolated lignin with a series of dimeric and trimeric tricin-4′–O–β-ether model compounds. Results showed that the tricin moiety significantly affects the chemical shift of the Cβ/Hβ of 4′–O–β unit, producing peaks at around δC/δH 82.5–83.5/4.15–4.45, that differ from the Cβ/Hβ correlations from normal 4–O–β units formed solely by monolignols, and that have to date been unassigned.